ANALISIS KONTROL MASYARAKAT TERHADAP KEBIASAAN KONSUMSI MIRAS DI KALANGAN REMAJA PADA PESTA PERNIKAHAN JORONG RANAH JAYA NAGARI KOTO GADANG KEC. KOTO BESAR KAB. DHARMASRAYA - Yatim, Yenita; Wahyuni, Emi; Erningsih, Erningsih (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2023)
The abuse of liquor in today's world is no longer limited to adults, but teenagers are not immune from the bad effects of drinking. The phenomenon of alcohol abuse by teenagers should not be taken lightly, because teenagers have a very important role for the survival of a nation. The purpose of this study is to describe the phenomenon of adolescents consuming liquor at a wedding in Jorong Ranah Jaya Nagari Koto Gadang, Koto Besar District, Dharmasraya Regency. The theory used in this study is the theory of social Kontrol according to Petter L Berger. This research is a qualitative research using descriptive method. Data collection methods are through interviews and observation. Interviews were conducted with 20 informants, the informants in this study were taken using a purposive sampling technique. The data analysis model is through the stages of data collection, data reduction, data presentation and drawing conclusions. From the results of the research it was revealed that, First, the activity of consuming liquor at weddings in Jorong Ranah Jaya is a common thing, because the existence of liquor has been provided by the residents who have the event and have even been entrusted to the youth chairman and the Jorong chairman to make this happen. which gives freedom to anyone to consume liquor including teenagers. Second, the community's social Kontrol is carried out on teenagers who consume liquor, namely a) through parental supervision. Parents of children, even the head of Jorong and youth leaders must be actively involved in Kontrol ling the activities of teenagers who like to gather and drink alcohol at weddings. b) giving a warning, the community starting with the family and the social environment will try to measure every child's actions, both those who behave positively and even those who behave negatively, c) supervision of the environment in which they live. The social environment of children is closely related to the behavior they show and d) Witness/Punishment.